Integrating wildfire spread and evacuation times to design safe triggers: Application to two rural communities using PERIL model. (January 2023) - Mitchell, Harry; Gwynne, Steve; Ronchi, Enrico; Kalogeropoulos, Nikolaos; Rein, Guillermo
Abstract: The hazards posed by a wildfire increase significantly when it approaches the wildland–urban interface. Evacuation of rural communities is frequently considered by local authorities and residents. In this context, evacuation triggers are locations that when reached by the wildfire indicate it is time to evacuate. Triggers are often arbitrarily defined via identifiable landmarks, do not include a safety factor, and do not account for fire spread or how long the evacuation takes. Ill-designed triggers may not safely inform decision making. It is necessary to create evacuation triggers that take into account both how a fire spreads towards the community, and how a community evacuates. This paper outlines a framework for developing triggers through the coupling of wildfire and evacuation models. We implement the previous theory of Cova et al. (2005) and others on triggers into a tool known as PERIL for generating trigger perimeters around a community, using the fire spread model FARSITE. A safety factor is included to address uncertainties in the wildfire or evacuation calculations. PERIL was applied to two real communities for the Swinley forest community (UK), and Roxborough Park community (USA). These communities were chosen because of previous work studying their actual evacuations. PERIL, which is available in open source, can be applied to inform safer strategies for to protect rural communities threatened by wildfires. Graphical abstract: Highlights: Integration of wildfire models with actual and simulated evacuation data to develop trigger perimeters. Development of simplified test cases for trigger perimeter generation. Application to two rural communities: Swinley Forest, UK, and Roxborough, USA. Development of safety factors for trigger perimeters. Insights into the design of trigger perimeters to help inform safe evacuations.